Pengaruh Opini Audit, Pergantian Manajemen, Ukuran Perusahaan dan Ukuran KAP terhadap Auditor Switching Pada Perusahaan Pertambangan - Hidayatulloh, Taufik; Amyar, Firdaus; Djanegara, Moermahadi; Dzulkarnaen, Pingky Dezar (Institut Bisnis dan Informatika Kesatuan, 2022)
For companies, auditor turnover is an important thing to do as a way to maintain the independence of the auditor when conducting an audit of the company. Through third parties, namely the company's auditors, they can find out whether the presentation of financial statements by management will look fair or unfair in their presentation. This study was conducted to determine the effect of audit opinion, management turnover, company size and hood size on auditor switching in mining companies listed on the Indonesia Stock Exchange. This research is a quantitative research, and the source of the data obtained is secondary data. The population of this study are mining companies listed on the Indonesia Stock Exchange. The sample of this research is 30 mining companies using annual financial statements and has complete data with the variables used during 2017-2019. Sampling for the study was determined by purposive sampling. The dependent variable in this study is auditor switching and the independent variables are audit opinion, management turnover, company size and public accounting firm size. The method in this study uses documentation and data analysis using logistic regression analysis. The results show that the value of Nagelkerke R Square is 0.106, which means that audit opinion, management turnover, company size, and public accounting firm size can explain 10.6% of auditor switching and the rest is influenced by other variables outside of this study. Based on the results of the partial test, it shows that management turnover has an effect on auditor switching, while for audit opinion, company size and hood size have no effect on auditor switching. Based on the results of the simultaneous test, it shows that the audit opinion, management turnover, company size and the size of the public accounting firm simultaneously have no effect on auditor switching. Keywords: audit opinion, management turnover, company size, public accounting firm size, auditor switching.